The Effect of Blue Light Exposure on Retinal Health and Visual Function: A Clinical Study of 160 Patients - Syed Noor, Iftikhar Ul Haq Tareen, Abdul Munim, Mohammad Afzal Khan, Tariq Pervaiz Khan, Abdul Rafe (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Blue light, a high-energy visible light emitted by digital screens and LED lighting, has gained attention for its potential effects on retinal health and visual function. Prolonged exposure to blue light may cause oxidative damage to retinal cells, contributing to conditions such as age-related macular degeneration (AMD), digital eye strain, and myopia progression. While the scientific community has explored the impact of blue light on retinal health in laboratory settings, clinical data on human populations remain sparse. Methodology: This cross-sectional study involved 160 patients (aged 18-65) who were categorized based on their screen exposure time (high exposure: ≥6 hours/day, low exposure: 3-6 hours/day). Retinal health was assessed using Optical Coherence Tomography (OCT), visual acuity was measured using Snellen charts, and the Computer Vision Syndrome (CVS) questionnaire was used to assess digital eye strain symptoms. The refractive error was measured with autorefractors to track myopia progression. Statistical analysis was performed using independent t-tests and chi-square tests to evaluate the differences between high and low exposure groups. Results: The results showed a significant association between prolonged blue light exposure and retinal damage, including increased retinal nerve fiber layer thickness and foveal thickness in the high exposure group. Visual acuity was significantly reduced in the high exposure group (0.4 ± 0.3 logMAR) compared to the low exposure group (0.1 ± 0.2 logMAR). The prevalence of digital eye strain was higher in the high exposure group (65%) compared to the low exposure group (42%). Furthermore, myopia progression was observed in 35% of high exposure participants, compared to 12% in the low exposure group. The findings were statistically significant (p < 0.05). Conclusion: Prolonged exposure to blue light is associated with retinal damage, reduced visual acuity, digital eye strain, and accelerated myopia progression. These findings highlight the need for preventive measures such as screen time management, blue light filtering glasses, and regular eye health assessments to mitigate the potential risks associated with prolonged blue light exposure. Keywords: Blue light, Retinal health, Visual function, Age-related macular degeneration, Digital eye strain, Myopia progression, Ophthalmology, Eye health, Screen time, Blue light filtering.